Índice de calidad de agua de las fuentes hídrica que abastecen al ganado bovino, parroquia Quiroga - Cajape Bravo, José Francisco (2021)
In order to know which are the most used water sources to supply cattle in Quiroga parish, Bolívar canton, Julián, La Pavita, Corcovado, Tablon Verde and Patón sites were selected respectively, and a survey was carried out to identify them. The most useful water source, for this a stratified random sampling was used, to then sample the most used water source, where the Water Quality Index (ICA) was applied, National Sanitation Foundation of the United States (NSF). The data was processed through the Advanced Excel statistical tool that allowed to know the frequency of data obtained in the survey, in which the result of this non-experimental research indicates that 85% of the farmers use water that comes from springs to direct consumption of livestock, the points taken for water sampling in the studied sectors were Julián, La Pavita, Corcovado and Tablón Verde, which presented a “Good” quality with a sum of the index / 100 of 76, 83%, 71.14%, 72.05% and 71.04% respectively, while the Patón site witnessed a “Medium” quality with 56.57% given by the presence of Coliforms in the water. For a better use and conservation of water quality, it was suggested as a proposal to encourage the application of artificial drinkers in cattle farms, information that was shared with the farmers with the use of triptychs containing relevant information.